2021
DOI: 10.3389/fcell.2020.618536
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNAs as Regulators of Immune and Inflammatory Responses: Potential Therapeutic Targets in Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is the principal cause of end-stage renal disease and results in high morbidity and mortality in patients, causing a large socioeconomic burden. Multiple factors, such as metabolic abnormalities, inflammation, immunoregulation and genetic predisposition, contribute to the pathogenesis of DN, but the exact mechanism is unclear, and the therapeutic strategies are not satisfactory. Accordingly, there is an unmet need for new therapeutic targets and strategies for DN. MicroRNAs (miRNAs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 104 publications
0
29
0
Order By: Relevance
“… 42 , 43 In recent years, studies have revealed that some miRNAs could be regulators of immune and inflammatory responses and are potential therapeutic targets in DN. 15 , 16 Single nucleotide polymorphisms of miRNA-related genes can affect the production, expression, and function of mature miRNAs, thus affecting disease susceptibility and the immune response. We identified the differentially expressed miRNAs in DN using the GSE161884 dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 , 43 In recent years, studies have revealed that some miRNAs could be regulators of immune and inflammatory responses and are potential therapeutic targets in DN. 15 , 16 Single nucleotide polymorphisms of miRNA-related genes can affect the production, expression, and function of mature miRNAs, thus affecting disease susceptibility and the immune response. We identified the differentially expressed miRNAs in DN using the GSE161884 dataset.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Studies have revealed that some miRNAs could be regulators of immune and inflammatory responses and are potential therapeutic targets in DN. 15 , 16 However, there have been few studies on genetic variation in miRNA and complement levels in diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is noteworthy to be mentioned that non-coding RNAs (ncRNAs) that are located in the seven cytogenetic regions identified from the meta-analysis could further regulate gene expression. Roles of microRNA (miRNA), long ncRNA (lncRNA) and circular RNA (circRNA) in DN have recently studied [ 65 67 ]. MiRNA is the best characterized non-coding RNA for transcriptional gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs) commonly include transfer RNA, ribosomal RNA, long ncRNA (lncRNA), small ncRNA (e.g., microRNA, piRNAs, snoRNA, snRNA, exRNA) and circular RNA (circRNA) ( Storz, 2002 ; Yang, 2015 ). Roles of microRNA (miRNA), lncRNA and circRNA in DN have been recently studied ( Loganathan et al, 2020 ; Zhou et al, 2021 ). MiRNA is the best characterized non-coding RNA for transcriptional gene regulation by targeting the 3′-UTR of a specific mRNA.…”
Section: Dn and Epigenetic Modifications Involved In Inflammationmentioning
confidence: 99%
“…MiRNAs play significant roles in regulating inflammation in DN ( Zhou et al, 2021 ). Recent studies involving models of DN podocytes have found that downregulation of the miR-17∼92 cluster ameliorates inflammation and podocyte injury by targeting ABCA1 (ATP-binding cassette transporter A1) ( Fan et al, 2020 ).…”
Section: Dn and Epigenetic Modifications Involved In Inflammationmentioning
confidence: 99%